HEALTH CARE POLICY OF THE YOUNG BUKHARIAN GOVERNMENT - Nuridinov Turdali Qambarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Studying the history of the people and its rich cultural heritage, promoting them among the broad strata of the population is one of the most important tasks for the modernizing Uzbekistan. President of the Republic of Uzbekistan Sh. M. Mirziyoev, the issue is "first of all, it is about creating the necessary environment and conditions for the wide promotion of the rich history of our country, its unique culture and national values ​​among the youth and the population, and for conveying the achievements of world science and literature" [January 16, 2017] , he noted.